What do we know about research on parasport coaches? A scoping review - Bentzen, M.; Alexander, D.; Bloom, G. A.; Kenttä, G. (Adapted Physical Activity Quarterly, 2023)
The purpose of this scoping review was to provide a broad overview of the literature pertaining to parasport coaches, including information regarding the size and scope of research, the populations and perspectives obtained, and the type of methods used to conduct the research. Data were collected and analyzed using a six-stage framework for conducting scoping reviews. The results revealed that the majority of articles were based on interviews, and an overwhelming majority of the participants were men coaching at the high-performance level in North America. Three of the most frequent topics were becoming a parasport coach, being a parasport coach, and having general parasport coaching knowledge. Articles ranged in date from 1991 to 2018, with 70% of empirical articles published from 2014 onward, indicating an emerging interest in this field of research. This review has the potential to advance the science and practice of parasport coaching at all levels.